Platform work – controversies surrounding the practice of its use - Spytek-Bandurska, Grażyna (The use of atypical forms of employment in violation of labour and social security laws - diagnosis and prospects for the future, 2023)
The aim of the article is to present the uniqueness of platform work as an element of the sharing economy. Platform work is one of the unusual forms of employment that is developing dynamically on the labour market as a result of progressing computerization and the emergence of modern technologies. Its essence is to connect (match) customers with service providers via mobile applications and online platforms. It is usually associated with on-demand passenger transport and food delivery. In fact, it covers a wide variety of specialized assignments. The complexity of platform work is evidenced by the difficulties in defining its conceptual scope and giving the performers the appropriate legal status. The role of algorithms is unclear. As a result, it does not seem possible to regulate this form in an unambiguous, precise and universal manner, which is confirmed by the long-lasting EU negotiations.